2016
DOI: 10.5771/0949-6181-2016-2-139
|View full text |Cite
|
Sign up to set email alerts
|

Emerging advanced topics in an advanced emerging market? International business research in Poland in the period 1990-2014

Abstract: The main objective of this paper is to present the findings of a structured review of contributions to international business research in Poland in the period 1990-2014. In order to address this objective, qualitative and quantitative methods were integrated to identify main research areas, their relative importance and changes thereof within the analysed timeframe, as well as specific research topics within each area. The results indicate that macro-and micro-level internationalisation, followed by internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Remiantis Puślecki et al (2016), tarptautinio verslo reikšmė gali būti analizuojama makro-, mezo-ir mikrolygmeniu. Analizuojant makrolygmeniu apibūdinama tarptautinio verslo svarba šalies mastu; nagrinėjant mezolygmeniui, tarptautinio verslo svarba regionų kontekste, o mikrolygmuo padeda nustatyti atitinkamo socialinio subjekto (verslo vieneto) situaciją, atsižvelgiant į socialinio subjekto finansinius, žmogiškųjų išteklių, konkurencingumo ir kt.…”
Section: Tyrimo Metodikaunclassified
“…Remiantis Puślecki et al (2016), tarptautinio verslo reikšmė gali būti analizuojama makro-, mezo-ir mikrolygmeniu. Analizuojant makrolygmeniu apibūdinama tarptautinio verslo svarba šalies mastu; nagrinėjant mezolygmeniui, tarptautinio verslo svarba regionų kontekste, o mikrolygmuo padeda nustatyti atitinkamo socialinio subjekto (verslo vieneto) situaciją, atsižvelgiant į socialinio subjekto finansinius, žmogiškųjų išteklių, konkurencingumo ir kt.…”
Section: Tyrimo Metodikaunclassified
“…Almost the same is true when it comes to the internationalization of Polish high-tech firms (Daszkiewicz, 2019;Głodowska et al, 2023b). As indicated in 2016, there were only a few papers linking internationalization and technology in the context of Polish firms over the quarter-century period of 1990-2014 (Puślecki et al, 2016).…”
mentioning
confidence: 93%
“…There are currently not many studies from emerging economies on international entrepreneurship (Perényi & Losoncz 2018;Głodowska 2019;Puślecki et al, 2016). Another viewpoint on this issue is that Poland is an emerging market -the post-transition economy.…”
mentioning
confidence: 99%
“…Jaklič et al (2020) identified trends in CEE-related international business research but also encompassed studies that focused on the role of institutions in the region. Puślecki et al (2016) only encompassed Polish authors’ studies on Polish firms’ outward and inward international activities. Éltető (2019) conducted a literature review on CEE and Iberian exporters’ recovery from the 2008 to 2009 financial crisis.…”
Section: Introductionmentioning
confidence: 99%